2005
DOI: 10.1103/physrevlett.94.047602
|View full text |Cite
|
Sign up to set email alerts
|

Texture in the Superconducting Order Parameter ofCeCoIn5Revealed by Nuclear Magnetic Resonance

Abstract: We present a 115In NMR study of the quasi-two-dimensional heavy-fermion superconductor CeCoIn5 believed to host a Fulde-Ferrel-Larkin-Ovchinnikov (FFLO) state. In the vicinity of the upper critical field and with a magnetic field applied parallel to the ab plane, the NMR spectrum exhibits a dramatic change below T*(H) which well coincides with the position of reported anomalies in specific heat and ultrasound velocity. We argue that our results provide the first microscopic evidence for the occurrence of a spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
117
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(119 citation statements)
references
References 30 publications
2
117
0
Order By: Relevance
“…[7][8][9] In magnetic fields, the spin degrees of freedom are significantly coupled with the stability of the SC order; a strong Pauli paramagnetic effect gives rise to a first-order transition at the SC upper critical field H c2 below 0.7 K, 7,[10][11][12] and the SC phase coexistent with AFM spin modulation evolves just below H c2 at very low temperatures. [13][14][15][16][17][18] Furthermore, the existence of the AFM-QCP at ∼ H c2 is strongly suggested from the observations of the NFL behavior in the paramagnetic phase above H c2 , including the − ln T divergence in specific heat divided by temperature, the T -linear dependence in magnetization, and electrical resistivity. 10,19,20) In fact, the long-range AFM orders are generated by substituting the ions for the elements in CeCoIn 5 , such as Nd for Ce, 21,22) Rh for Co, [23][24][25][26] and Cd, Hg, and Zn for In.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In magnetic fields, the spin degrees of freedom are significantly coupled with the stability of the SC order; a strong Pauli paramagnetic effect gives rise to a first-order transition at the SC upper critical field H c2 below 0.7 K, 7,[10][11][12] and the SC phase coexistent with AFM spin modulation evolves just below H c2 at very low temperatures. [13][14][15][16][17][18] Furthermore, the existence of the AFM-QCP at ∼ H c2 is strongly suggested from the observations of the NFL behavior in the paramagnetic phase above H c2 , including the − ln T divergence in specific heat divided by temperature, the T -linear dependence in magnetization, and electrical resistivity. 10,19,20) In fact, the long-range AFM orders are generated by substituting the ions for the elements in CeCoIn 5 , such as Nd for Ce, 21,22) Rh for Co, [23][24][25][26] and Cd, Hg, and Zn for In.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays such states are collectively known as the Fulde-FerrellLarkin-Ovchinnikov (FFLO) state. Recently the FFLO state has received renewed interest due to experimental evidence of its existence in various superconductors, 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27 and the (thus far theoretical) possibility of its realization in trapped cold atom systems, 28,29 nuclear matter and in the core of neutron stars. 30 Soon after the original work of FFLO, it was found that the FFLO state is very sensitive to the presence of impurities, and eventually suppressed when the disorder strength reaches certain critical value.…”
Section: Introductionmentioning
confidence: 99%
“…It follows from the fact that they possess properties close to heavy fermions systems [16], for which strong experimental evidence suggest the existence of said phase [17][18][19][20][21][22]. Both kinds of systems are multilayered, clean and have a relatively high Maki parameter.…”
mentioning
confidence: 99%